Effect of Moringa oleifera Leaf Flour Supplementation on Magnesium (Mg) and Potassium (K) Contents of Crackers as a Nutritious Snack - Desi Desi; Abd Hakim Laenggeng; Masrianih Masrianih; Musdalifah Nurdin; Raya Agni; I Nengah Kundera (Biology, Medicine, & Natural Product Chemistry, 2026)
Moringa oleifera leaf flour is recognized as a local food ingredient rich in essential minerals, particularly magnesium (Mg) and potassium (K), which play important roles in various physiological functions of the human body. This study was conducted to evaluate the effect of Moringa oleifera leaf flour supplementation on the magnesium and potassium contents of crackers. The research employed an experimental approach using a Completely Randomized Design (CRD) consisting of four treatments: 0%, 5%, 10%, and 15% Moringa oleifera leaf flour supplementation, with two replications for each treatment. Magnesium and potassium contents were quantitatively determined using the Atomic Absorption Spectrophotometry (AAS) method. The data were analyzed using One-Way Analysis of Variance (ANOVA) at a significance level of 0.05. The results showed that increasing concentrations of Moringa oleifera leaf flour tended to increase the magnesium and potassium contents of the crackers, with magnesium levels ranging from 0.06 to 0.09 mg/g and potassium levels ranging from 0.79 to 1.93 mg/g. However, statistical analysis revealed that the addition of Moringa oleifera leaf flour did not significantly affect magnesium content (p = 0.377), whereas it had a significant effect on potassium content (p = 0.001). These findings indicate that magnesium and potassium responded differently to the fortification process. Therefore, Moringa oleifera leaf flour demonstrates considerable potential as a fortification ingredient, particularly for enhancing potassium content in crackers as a nutritious snack alternative.